Impact of Pocari and Mineral drinks on pulse rate after running 1200 meters with a 5-minute rest interval - Gunawan, Dede; Custodio, Joselito M.; Suniga, John Paul C.; Laoan, Menard Ian; Stojmenović, Dragutin (Tanjungpura Journal of Coaching Research, 2023)
Background and Study Aim. Electrolyte drinks are ion replacement drinks in the body that also help as additional energy.  Moreover, it is said that this drink is not a drug because it has not been clinically tested so that it is included in the list and also complementary drinks have benefits and side effects for its users, of course, supplement drinks that isotonic drinks affect dehydration and isotonic drinks can normalize body fluids that have been lost during exercise. The purpose of this study was to determine the difference in the usefulness of Pocari and Mineral for fluids in the body after prolonged exercise.Material and Methods. This research is an experimental method. The population in this study were Tanjungpura University Sports Students Semester 5 with a total of 18 people divided into 2 groups so each group contained 9 people. In this study, the sample was given physical activity treatment through running 1200 meters. Furthermore, Pcoari and Mineral drinks were given to see the effect on pulse rate. Data analysis was assisted using SPSS 26.Results. The results show a significance value of 0.173 > 0.05 so it can be concluded that the data results of pocari water and mineral water do not experience significant differences. These results provide information that provides the same impact on pulse rate after physical activity. However, the mean value results show that mineral water (162.56) is smaller than pocari drinks (175.00).Conclusions. This result has important implications, especially for athletes or individuals engaged in similar sports activities. Consumption of mineral-containing isotonic drinks may be an effective strategy in supporting the body's recovery after physical exercise, thereby improving overall sports performance.